Hyperoxygenation in Pregnancy Exerts a More Profound Effect on Cardiovascular Hemodynamics Than is Observed in the Nonpregnant State. Issue 2 (June 2020) - McHugh, A.; El-Khuffash, A.; Bussmann, N.; Doherty, A.; Franklin, O.; Breathnach, F.
Abstract : ( Am J Obst Gynecol . 2019;220:397.e1–397.e8) Supplemental oxygen, or hyperoxygenation, in the pregnant population is used in a number of clinical scenarios. Studies have shown that maternal hyperoxygenation (MHO2 ) improves fetal oxygen levels and fetal heart rate (FHR) patterns. Yet, we lack data to demonstrate improvement in maternal and neonatal outcomes with this therapy. Despite wide use of hyperoxygenation in obstetric practice, there is also no clear guidance on indication, dose range, duration, and benefit. This study aimed to compare the effect of hyperoxygenation on cardiac index, systemic vascular resistance (SVR), stroke volume, blood pressure, and heart rate in third trimester pregnant women to the hemodynamic effects of hyperoxygenation in nonpregnant women.